The Role of Government and Community Participation in the Success of School Feeding Programs in Secondary Schools in Tanzania - Chacha, Gisiri; Biswalo, Upendo P. (Journal of Education and Practice, 2025)
Purpose: School feeding programs are increasingly recognized as strategic interventions to improve student attendance and educational equity. Globally, these initiatives have shown positive effects on learners’ retention and academic performance. In Tanzania, particularly in rural areas like Kongwa District, school feeding programs are implemented amid logistical and community-level challenges. The purpose of this paper was to assess the role of government and community participation in the implementation of feeding programs in secondary schools in Kongwa district, Dodoma-Tanzania. Methodology: The study employed a mixed-methods approach within a descriptive research design to assess the perceived impact of feeding programs on student attendance in secondary schools. Purposive sampling was used to select 5 schools, from which 30 students and 10 teachers were involved through questionnaires, interviews, and document analysis. Quantitative data was analyzed using descriptive statistics, while qualitative data were examined thematically. Findings: Findings revealed that limited community participation and low awareness, poverty, inadequate funding from the government, and limited alignment of national feeding programs’ policies and implementation affect the sustainability of programs in the selected secondary schools in Kongwa, Dodoma. Unique Contribution to Theory, Practice and Policy: The study recommended stronger policy enforcement, strengthening community/ parental participation and ownership are crucial for feeding programs’ success and overall students’ well-being. Moreover, the government should provide more funds to ensure the sustainability of the feeding programs in secondary schools in Tanzania.